Interpreting Chekhov's prose - Polakiewicz, Leonard A. 1938- (Ars Rossica, 2024)
"Works examined include those dealing with Chekhov's astonishingly accurate and artistic portrayal of a wide variety of illnesses, sans any use of medical terms. These works are shown to be not mere "clinical studies," but genuine, impressive works of art. The author who suffered half of his life from tuberculosis, understandably, portrayed effectively many characters afflicted with this disease that was incurable at the time. Many of these works reveal an indisputable symbiosis of the doctor and the artist. Chekhov maintained that "in Goethe the poet lived amicably side by side with the scientist" - a fitting description of him as well. Doctors, the most frequently portrayed characters in Chekhov's oeuvre as well as their plight in nineteenth-century Russia, are appropriately subjected to extensive analysis and more of them than ever before. The themes of fate and death and dying that figure so prominently in Chekhov's oeuvre, are also treated extensively. Attention is accorded to imaginative fictional works dealing with philosophy and the theme of crime and punishment, as well as The Island of Sakhalin, a narrative of non-fictional sociological content."